Perspectives on Acute Hepatitis A Control in Korea - Kang, Seong Hee; Kim, Moon Young; Baik, Soon Koo (Journal of Korean medical science, 2019)
Until 1995, the incidence of symptomatic acute hepatitis A was minimal and there were no cases of national outbreak in Korea. However, there was a nationwide outbreak of hepatitis A that peaked in 2009. In 2019, a total of 10,083 cases of acute hepatitis A were reported for seven months of the year according to the Korea Center for Disease Control and Prevention. This may be attributed to the proportion of susceptible subjects in the Korean population, as about 10 years have passed since herd immunity was induced by the epidemic occurring during the late 2000s. Recent studies have shown that the rate of seropositivity for anti-hepatitis A virus antibodies (anti-HAV) is the lowest in adults in their 20s and has not changed much over the past 10 years, and seropositivity of anti-HAV in adults in their 30s has continued to decline from 69.6% in 2005 to 32.4% in 2014. Most young adults who have not yet experienced hepatitis A and are not vaccinated are vulnerable to hepatitis A infection. This year's epidemic of hepatitis A is a predictable outcome for vulnerable populations. Therefore, effective acute hepatitis A control and prevention strategies are needed, particularly for those in their 20s and 30s.